Imitation perfection - a simple rule to prevent discrimination in procurement - Helene Mass; Nicolas Fugger; Vitali Gretschko; Achim Wambach (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Procurement regulation aimed at curbing discrimination requires equal treatment of sellers. However, Deb and Pai (2016) show that such regulation poses virtually no restriction on the ability to discriminate. We propose a simple rule – imitation perfection – that restricts discrimination significantly. With homogeneous bidders, imitation perfection implies that all bidders earn the same surplus in every equilibrium conditional on their valuation.
Keywords: 330